Host suppression of quorum sensing during catheter-associated urinary tract infections. Issue 1 (December 2018) - Cole, Stephanie; Hall, Cherisse; Schniederberend, Maren; Farrow III, John; Goodson, Jonathan; Pesci, Everett; Kazmierczak, Barbara; Lee, Vincent
Abstract Chronic bacterial infections on medical devices, including catheter-associated urinary tract infections (CAUTI), are associated with bacterial biofilm communities that are refractory to antibiotic therapy and resistant to host immunity. Previously, we have shown thatPseudomonas aeruginosa can cause CAUTI by forming a device-associated biofilm that is independent of known biofilm exopolysaccharides. Here, we show by RNA-seq that host urine alters the transcriptome ofP. aeruginosa by suppressing quorum sensing regulated genes.P. aeruginosa produces acyl homoserine lactones (AHLs) in the presence of urea, but cannot perceive AHLs. Repression of quorum sensing by urine implies that quorum sensing should be dispensable during infection of the urinary tract. Indeed, mutants defective in quorum sensing are able to colonize similarly to wild-type in a murine model of CAUTI. Quorum sensing-regulated processes in clinical isolates are also inhibited by urea. These data show that urea in urine is a natural anti-quorum sensing mechanism in mammals. Pseudomonas aeruginosa can cause chronic infections on medical devices by forming biofilms, a process regulated by quorum sensing (QS). Here, the authors show thatP. aeruginosa is unable to perceive QS signals in the presence of either host urine or urea, and clinical isolates are often defective in QS.